Adverse effects of the new technologies and its interference in the learning process - Parra Reyes, David (2018)
This article allows us to show in a descriptive and analytical, based on scientific evidence of a social, psychological and clinical, those impact caused by the excess or abuse of digital technology through the use of cell phones or smartphones, tablets with access to the Internet, the, which bring as consequences to the child who uses it, metabolic repercussions such as obesity, functional repercussions such as visual fatigue, dizziness, anxiety or drowsiness; as well as psychological alterations in which the reactions of irritability predominate, behavior problems (tantrums, aggressiveness, little tolerance for frustration), insomnia, greater tendency to depression and even suicides (in the adolescent age). All these factors in turn interfere, in great magnitude, on their integral health and in the school learning process.